The Mechanics of Fear: Organic Haunted Houses in American Cinema - Anne-Marie Paquet-Deyris (Transatlantica)
Most haunted house narratives, whether literary or filmic, are based on the same basic principle of intrusion of some outside, usually unidentified force which sows the seeds of chaos and destruction within the boundaries of a home. What is particularly fascinating is precisely the way in which the group, and most often the family, reacts to this external force. But the whole point is also to determine the exact nature of the threat and to assess who—or what—the intruder is, so as to circumscribe “it” and return the community to some form of normality. In this respect, even though a direct descendant of a more conventional haunted house film genre, the 1980s family horror imposes a reversal of viewpoints. It actually seems to be reverting to some more classical Hollywood narrative structures after the bloodbaths of the previous decade in horror feasts, such as The Hills Have Eyes (1977) or Dawn of the Dead (1978), which argued then for a new form of society. It also demonstrates how the outside-the-norm entity is finally not considered exogenous any more but rather endogenous and how it appropriates and somehow tries to incorporate some, if not all, members of the household. In his 1981 film The Entity, Sidney Furie stages Barbara Hershey’s body (Carla Moran) as a vehicle for the revelation process and in their 1982 Poltergeist, Tobe Hooper and Steven Spielberg also use young Heather O’Rourke (Carol Anne Freeling) as a medium in very different kinds of houses, no longer darkened and isolated in some desolate part of the American East Coast but now part of the West Coast urban sprawl. Not unlike the next houses on the block, sometimes even belonging to the same housing development, they nevertheless come alive through the impetus given by some obscure catalizer. The same question reemerges: what are the true nature and impact of the haunting in such nondescript places?